Ultra high voltage gain non-isolated DC-DC converter based on new interleaved triple boosting technique - Algamluoli, Ammar; Wu, Xiaohua; Abdulhadi, Haider M.; Kitmo,; Khan, Malak Adnan (Frontiers in Energy Research, 2023)
This paper introduces a DC-DC converter that employs a modified triple boosting architecture (MTB), interleaved with modified switched inductor capacitors (MSIC), to achieve ultra-high voltage gain in photovoltaic applications. The converter design also includes a modified switched inductor with a modified voltage multiplier mode (MVM), which interleaves with the main switch and effectively doubles the voltage transfer gain. Furthermore, a modified triple boosting mode technique, utilizing interleaved components and an auxiliary switch, is integrated into the converter design. The main switch and auxiliary switch, combined w ith modified voltage multiplyer, contribute to achieving high voltage gain. The proposed converter offers numerous advantages. It exhibits remarkable efficiency while ensuring low voltage stress across diodes and MOSFETs. Moreover, by utilizing low inductance and capacitance values at high switching frequencies, the converter's overall performance is enhanced. To validate and substantiate the simulation and laboratory results, the converter has undergone PCB design and experimental testing. Specifically, this converter is designed to boost input voltage levels ranging from 30V to 40V to a variable output voltage between 200V and 400V, with a power output of 360 watts and an efficiency rating of 96.5%.